Frailty predicts surgical complications after kidney transplantation. A propensity score matched study - dos Santos Mantovani, Milena [UNESP]; de Carvalho, Nyara Coelho [UNESP]; Archangelo, Thomáz Eduardo [UNESP]; de Andrade, Luis Gustavo Modelli [UNESP]; Filho, Sebastião Pires Ferreira [UNESP]; de Souza Cavalcante, Ricardo [UNESP]; Kawano, Paulo Roberto [UNESP]; Papini, Silvia Justina [UNESP]; Costa, Nara Aline [UNESP]; de Barros Almeida, Ricardo Augusto Monteiro [UNESP] (Public Library of Science (PLoS), 2020)
Background and objective Surgical complications after kidney transplantation can lead to catastrophic outcomes. Frailty has been associated with important kidney transplantation outcomes; however, there are no studies assessing this measure of physiological reserve as a specific predictor of surgical complications in this population. Such an assessment was, therefore, the objective of the present study. Methods A total of 87 individuals aged ≥ 18 years who underwent kidney transplantation between March 2017 and March 2018 were included. At the time of admission for kidney transplantation, demographic, clinical, and kidney transplantation data were collected, and the frailty score was calculated according to Fried et al., which comprises five components: shrinking, weakness, exhaustion, low activity, and slowed walking speed. Urological, vascular, and general surgical complications were assessed three months later, or until graft loss or death. The propensity score was used to achieve a better homogeneity of the sample, and new analyses were performed in this new, balanced sample. Results Of the 87 individuals included, 30 (34.5%) had surgical complications. After propensity score matching, the risk of surgical complications was significantly higher among the frail individuals (RR 2.14; 95% CI 1.01–4.54; p = 0.035); specifically, the risk of noninfectious surgical complications was significantly higher among these individuals (RR 2.50; 95% CI 1.11–5.62; p = 0.017). Conclusion The results showed that individuals with some degree of frailty before kidney transplantation were more subject to surgical complications. The calculation of the frailty score for transplant candidates and the implementations of measures to increase the physiological reserve of these patients at the time of kidney transplantation may possibly reduce the occurrence of surgical complications.